PHASAL REALIZATIONS IN CLASSROOM DISCOURSE A Systemic-Functional Analysis - Simbolon, Lasyuli (TABULARASA, 2014)
This article examines the phasal realizations characteristic of the classroom discourse. The data are collected by means of audio-visual recordings and transcriptions, and they are analyzed by employing a complementary method of analysis of Youngâs model. The primary instrument of this study is the researcher herself, whereas the secondary instruments are (1) classification schemes of the semiotic aspect in focus, (2) data sheets that contain 4 classroom discourse-in-texts, and (3) notes on each classroom discourse-in-text. The findings reveal that the CD-in-text as a whole is typically realized and characterized by the following: (1) Substantiation (SU) as the most prominent macro-function and the Conclusion (CO) as the least prominent, (2) the Interchange (IC) as the most prominent micro-function and the Apology (AP) as the least prominent. Based on the main findings, there is strong evidence to suggest that the âsemiotic behaviorâ of the CD-in-text as a whole is motivated by the goal-oriented need, and the goal to achieve has tended to be more academic-oriented than social-oriented. In this, the teachers as the primary speakers of the classroom interactions have tended to focus on the transformation of intellectual values (academic knowledge/skills) with the least social values involved therein. The most prominently occurring SU macro-function and IC micro-function are clear indicators of this endeavor. The scope and the objectives of this study have been delimited to investigate CD phenomena at the levels of phase and sub-phase.